Minimally Invasive Surgery for Sternoclavicular Joint Infection with Osteomyelitis, Large Abscesses, and Mediastinitis. (22nd October 2022) - Ota, Hideki; Ishida, Hirotaka; Matsumoto, Hidekazu; Ishiyama, Tomoharu
Abstract : Background . Sternoclavicular joint infections require en bloc resection for radical cure; however, this aggressive procedure may result in multiple adverse events. Therefore, performing minimally invasive surgery is desirable. In this report, we describe a case of sternoclavicular joint infection complicated by osteomyelitis, large abscesses, and mediastinitis that was successfully treated with incision and drainage. Case Presentation . A 42-year-old man with no medical history presented to our hospital with complaints of painful swelling in the left chest wall and acute dyspnea. Computed tomography revealed arthritis of the left sternoclavicular joint, osteomyelitis of the clavicle and sternum, anterior mediastinitis, and abscesses in the neck, chest wall, and retrosternal and extrapleural spaces. Gram staining of the aspirated pus revealed clusters of gram-positive cocci. A diagnosis of Staphylococcus aureus sternoclavicular joint infection with locoregional spread was made. Emergency surgery was performed following adequate resuscitation. A skin incision was made in the second intercostal space. The joint capsule was widely opened, necrotic tissue was curetted, and closed suction drains were placed in the abscess cavities and connected to a negative pressure system. The wound was then closed using primary sutures. The postoperative course was uneventful. Methicillin-sensitive Staphylococcus aureus was cultured from the pus. The patient was discharged on postoperative day 14. Osteomyelitis worsened within a few weeks after surgery but recovered with wound management and six weeks of antibiotic therapy. The patient has had no recurrence of infection for two years. Conclusions . Incision and drainage proved to be an effective minimally invasive surgical treatment for sternoclavicular joint infection with osteomyelitis, large abscesses, and mediastinitis caused by methicillin-sensitive Staphylococcus aureus .